1995
DOI: 10.1111/j.1540-6261.1995.tb05174.x
|View full text |Cite
|
Sign up to set email alerts
|

Stock Volatility and the Levels of the Basis and Open Interest in Futures Contracts

Abstract: This article tests a theoretical model of the basis and open interest of stock index futures. The model is based on the differences between stock and futures in terms of investors' ability to customize stock portfolios and liquidity. Empirical evidence confirms the model's prediction that increased volatility decreases the basis and increases open interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 23 publications
(17 reference statements)
4
33
0
1
Order By: Relevance
“…Very few research studies have examined the leadlag behaviour between future market depth and spot volatility (Bessembinder & Seguin, 1992, 1993Chen et al, 1995;Yang et al, 2005). (…”
Section: Relationship Between Depth In the Future Market And Spot Volmentioning
confidence: 99%
“…Very few research studies have examined the leadlag behaviour between future market depth and spot volatility (Bessembinder & Seguin, 1992, 1993Chen et al, 1995;Yang et al, 2005). (…”
Section: Relationship Between Depth In the Future Market And Spot Volmentioning
confidence: 99%
“…However, Canina and Figlewski (1993) study the S&P 100 Index options for the period March 15, 1983to March 28, 1987 and document that implied volatility (IV) computed using BlackScholes options pricing formula is inefficient, biased and inferior estimate of market's future volatility forecast, when com pared to historical volatility. Chen, Cuny and Haugen (1995) study the relationship between stock volatility, basis 2 and open interests in futures market using S&P 500 Index. They base their study on the intuition that when volatility increases in the market, inves tors prefer to entice more people in the market for risk shar ing.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to many previous empirical studies on stock index futures, we use the following lag‐3 regression model for the basis: normalbnormalanormalsnormalist=β0+β1normalbnormalanormalsnormalisitalictnormal−1+β2normalbnormalanormalsnormalisitalictnormal−2+β3normalbnormalanormalsnormalisitalictnormal−3+γnormalvnormalolt+αnormalDnormalunormalmnormalmyt, where the variables are defined as follows: the basis of the index at time t; the volatility of the index at time t; indicates if there is a change in the margin requirement or the position limit for the index (0, no change; +1, increase; 1, decease). In (10), the volatility and the change in the margin requirement or the position limit are independent variables. The reason we include the volatility as an independent variable is based on earlier works which have shown that it has significant impact on the basis, for example, see Bailey and Stulz (1989), Hemler and Longstaff (1991), and Chen, Cuny, and Haugen (1995). In our empirical study, the volatility of an index is obtained by using the GARCH model based on its daily closing spot prices.…”
Section: Resultsmentioning
confidence: 99%